Enhanced Solar-Photocatalytic Degradation of Combined Chlorophenols Using Ferric Ions and Hydrogen Peroxide - Abeish, Abdul Basit Mohamad S.; Ang, Ha Ming; Znad, Hussein (American Chemical Society, 2014)
The influences of ferric ions (Fe3+) and hydrogen peroxide (H2O2) on the degradation of combined chlorophenols during solar/TiO2 process were investigated. 4-Chlorophenol (4-CP) and 2,4-dichlorophenol (2,4-DCP) were used as a chlorophenols combined mixture. Fe3+ ions have shown considerable effect on the solar-photocatalytic degradation rate of the mixture and its intermediates. Different amounts of Fe3+ ions were used, and the optimum value was 10 mg/L. At these conditions, three major intermediates were detected including hydroquinone (HQ), phenol (Ph), and 4-chlorocatechol (4-cCat). However, the concentrations of these aromatic intermediates were less than that of using TiO2 alone as well as the degradation time was reduced to 150 min. H2O2 was also effectively used as a degradation enhancer at various concentrations together with Fe3+ ions in order to improve the solar-photocatalytic degradation rate and the optimum value was 3.41 mM. The degradation efficiency of the combined mixture increased sharply in the presence of H2O2. Additionally, an extremely high degradation rate of the main pollutants and their intermediates was achieved when using Fe3+ ions and H2O2 together with TiO2. Furthermore, only two intermediates HQ and Ph were observed in this case. The complete degradation of the main chlorophenolic compounds and their intermediates was achieved within 130 min of solar irradiation.